Coping with the "small sample-small relevant effects" dilemma in elite sport research - Skorski, S.; Hecksteden, A. (International Journal of Sports Physiology and Performance, 2021)
Research in elite sport faces a characteristic tension between the inherently small number of elite athletes (and therefore lack of study participants) and the high relevance of even tiny differences. This characteristic constellation regularly leads to a mismatch of required and achievable sample size.